Overexpression and purification of YidRv gene from the hypervirulent Klebsiella pneumoniae, and the ability of the gene product in inducing a humoral response - Raras, Tri Yudani Mardining; Ajrullah, Mauludy Jutta; Gunawan, Ellen Fenix; Pramesti, Nadya Shafa; Prawiro, Sumarno Reto; Wardani, Agustin Krisna; Helianti, Is (Universitas Gadjah Mada, 2024)
The yidRv gene, isolated from the hypervirulent Klebsiella pneumoniae (hvKP), is a novel gene with an unknown function; however, it has exhibited high homology to the yidR, a gene recognized as potential vaccine candidate. The aim of this study was to clone the yidRv gene from the Indonesian hvKP and to investigate its overexpression in Escherichia coli. In the experiment, yidRv was cloned into pET21 to construct pYik23. Recombinant protein YidRv was produced by growing E. coli BL21 (DE3)/pYik23 in LB medium with ampicillin at 29 °C, inducing protein synthesis with 0.5 mM IPTG for 20 hours. Purification was performed using Ni‐NTA resin, and the purified protein (50 µg) was administered to BALB/c mice to test for the production of IgG, IgM and IgA on 2 days before and day 19th and 37th after the first vaccination. The results show a significant induction of IgG and IgM, but not of IgA antibodies. In conclusion, the yidRv gene was overexpressed in E. coli BL21 (DE3) at high levels in soluble form, with the recombinant protein able to be purified to 90% homogeneity. The recombinant YidRv demonstrated the ability to stimulate the generation of both IgM and IgG antibodies.